Is freeze-dried superfood kale supplementation healthier than common green peas? Outcomes of a cross-over trial - Aldisi, Dara; Sabico, Shaun; Almiman, Abeer; Al-Farraj, Amani; Basaeed, Taghreed A.; Wani, Kaiser; Hussain, Syed D.; Ansari, Mohammed G. A.; McTernan, Philip G.; Al-Daghri, Nasser M. (Frontiers in Nutrition, 2024)
Kale (Brassica oleracea species) is considered a functional food whose macronutrient and phytochemical contents are considered beneficial and widely considered as a superfood. In the present 6-week cross-over trial with a 2-week washout period, we compared the beneficial effects of freeze-dried kale over peas among Arab women with obesity. A total of 124 Saudi women with obesity were allocated to receive either freeze-dried kale (n=62) or freeze-dried peas (n=62) given in the form of 3-gram sachets thrice daily for two weeks, followed by a 2-week washout period and a cross-over of 4 weeks. Anthropometric measurements, glucose, lipids and markers of gut barrier function were assessed at baseline and post-intervention. Participants who took kale supplementation first resulted in significant weight reduction (p=0.02) which was not observed among those who took peas first. Participants receiving pea supplementation first experienced a significant decline in Hba1c (p=0.005) and CD14 (p=0.03), but C-peptide increased (p=0.05). Crossover analysis revealed significant carryover effects in most variables with non-significant combined treatment effects. Among the variables with no carryover effect with significant combined treatment effect include HbA1c which was in favor of the pea group (p=0.005) and C-peptide which was modestly in favor of the kale group (p=0.05). While both freeze dried kale and pea supplementation appear beneficial, supplementation of freeze-dried pea appears to be more effective in terms of acute glycemic control than kale. The study suggests that common but less-hyped vegetables such as pea maybe equally, if not more beneficial than the more expensive promoted superfoods such as kale. Longer clinical trials using a parallel design instead of cross-over are recommended to strengthen present findings.